Higher Snowfall Intensity is Associated with Reduced Impacts of Warming Upon Winter Snow Ablation. Issue 4 (13th February 2020) - Marshall, Adrienne M.; Link, Timothy E.; Robinson, Andrew P.; Abatzoglou, John T.
Abstract: Warming temperatures are altering winter snowpack accumulation and ablation. Physically based snowpack simulations have indicated that increasing precipitation intensity may buffer the impacts of warming on annual maximum snow water equivalents. Here, we assess this relationship using an observational dataset from the western United States and show that greater snowfall intensity is associated with reduced accumulation season ablation, particularly in warmer conditions. We also use outputs from a hydrological model to evaluate the effect of snowfall intensity on ablation in future climate scenarios. Snowfall intensity is projected to increase in the continental interior, which could reduce the average effects of warming on accumulation season ablation by as much as 6.3%, and decrease in maritime climates, increasing the effects of warming on ablation by up to 6.0%. These results indicate the importance of accurately modeling changing snowfall intensity and considering snowfall intensity in climate change impact assessments of snow‐dependent ecosystems and water resources. Plain Language Summary: The warming temperatures associated with climate change are impacting mountain snowpack, with major consequences for water resources. We assess the potential for snowfall intensity to mediate the effects of warming on midwinter snowmelt, finding that higher snowfall intensity is associated with reduced melt during the snow accumulation season. Our findings suggest that in the western United States, increased snowfall intensity in the continental interior will likely reduce the effects of warming on winter snowmelt, while decreased snowfall intensity in maritime regions will increase the effects of warming on winter melt. These findings underscore the importance of accurately capturing changes in precipitation intensity in climate change projections. Key Points: Winter snowfall intensity is associated with reduced accumulation season ablation, particularly at warmer winter temperatures Projected changes in snowfall intensity may exacerbate ablation in maritime western United States mountains and buffer losses in interior ranges As temperatures warm, a larger area will experience conditions in which snowpack ablation is sensitive to snowfall intensity